Political Propaganda, The Impact Of The Election Campaign, The Electoral Outcome, And The Dynamics Of Governance In Nigeria Following The 2015 Presidential Election - Ajiteru,S.A.R; Sulaiman T.H (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study assesses how campaign propaganda affected Nigeria's post-election government and the results of the 2015 presidential election. It examines in detail how ethno-religious campaigns The winning party's policy orientation, the victory of an opposition party, and the rational voting decisions of individuals were all influenced by the messaging of the two main political parties. To accomplish their goal of garnering more votes, politicians from all over the world adorn their language in distinctive ways to give their message more impact and force. Repetition, promise, colloquialism, word coinages, pidginized, and metaphorical language are some ways that rhetoric and propaganda can embody this. The figurative terms' denotative and connotative meanings are examined. It is believed that hyperbole, rhetorical inquiries, and rude remarks are characteristics of propaganda as a subset of this register. Therefore, political actors and foreign interests willingly used the media to disseminate divisive views. and a smear campaign against alleged rivals. Evidence suggests that the winning party has not significantly fulfilled its electoral promises five years after political ascendancy, despite the fact that campaign propaganda containing hate speech and dubious information helped an incumbent lose the 2015 Nigerian presidential election.